HUBUNGAN ASUPAN PROTEIN, ASUPAN FOSFOR DAN RASIO FOSFOR-PROTEIN DENGAN KADAR FOSFOR DARAH PADA PASIEN PENYAKIT GINJAL KRONIS DENGAN HEMODIALISIS RUTIN DI YAYASAN GINJAL DIATRANS INDONESIA 2010 - , Ahmad Syauqy, Susetyowati, DCN., M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Chronic Kidney Disease (CKD) has become a public health problem worldwide. Hemodialysis (HD) is a therapy for patients with terminal CKD. Hyperphosphatemia is one cause of mortality of CKD patients on routine HD. Correction and prevention of hyperphospatemia is a major component in the management of HD patients. High diet of protein in HD patients can cause increased concentration of phosphor serum due to mineral metabolism disorder associated with decreased function of renal glumerulous filtration rate. High protein intake is often followed by high phosphor intake because food containing high protein also contains much phosphor that will cause hyperphosphatemia. Meanwhile reduction of protein intake to control phosphor is associated with physical stamina. Good ratio of phosphor-protein is necessary to provide adequate protein intake and avoid hyperphosphatemia. Objective: To identify association between intake of protein, phosphor and ratio of phosphor-protein and level of blood phosphor in patients with CKD on routine HD. Method: The study was analytic observational that used cross sectional design with quantitative method. Data were obtained through food record, interview using questionnaire and laboratory test. Analysis used chi square at confidence interval 95%. Result: There was association between protein intake (p 0.037, RP 1.36, 95% CI 1.04-1.77), phosphor intake (p 0.005, RP 1.49, 95% CI 1.12-1.99) and ratio phosphor-protein (p 0.045, RP 1.39, 95% CI 1.08-1.79) and level of blood phosphor in CKD patients on routine HD. Conclusion: Protein intake was still needed to meet nutrition status but it should be considered to select source of protein that had low ratio of phosphor-protein. Source of phosphor as well as protein should be limited to sustain normal level of blood phospor. It was suggested to consume drugs that accurately and regularly bound phosphate.